Analisis Penggunaan Model Pembelajaran Inkuiri Terbimbing pada Materi Sejarah di Kelas 4 SD Negeri 079/II Baru Pusat Jalo - Pratama, Aditya Yoga; Saputra, Dandy; Haq, Kemal Amrul; Salim, Nur (Lembaga Yasin AlSys, 2023)
This article analyzes the implementation of the guided inquiry learning model in learning history in class IV SDN 079/II Baru Pusat Jalo. This study aims to test the effectiveness of guided inquiry learning in improving students' understanding of historical concepts and analytical skills. This study used a qualitative research design with a focus on class observation and student assessment. The guided inquiry learning model is applied in history learning, involving students in asking questions, conducting investigations, analyzing information, and drawing conclusions regarding historical events and topics. This study highlights the importance of guided inquiry learning in history education for fourth graders. It emphasizes the importance of students' active participation, inquiry-based approaches, and the integration of real-world connections to enhance historical understanding. The results provide insight into the potential benefits of implementing guided inquiry learning in other elementary school contexts.